Bahasa Media Sosial dan Pengaruhnya terhadap Penggunaan Bahasa Indonesia Anak Usia Madrasah Ibtidaiyah - Harahap, Diah Pahmasari; Nugraheni, Aninditya Sri (LP2M STAI Darul Kamal NW Kembang Kerang, 2026)
The rapid growth of social media has significantly influenced communication patterns and language habits of Madrasah Ibtidaiyah (MI) students, including their use of Indonesian in school settings. This study aims to explore the lived experiences of MI students in using Indonesian as shaped by social media language and to examine its implications for language practices in madrasahs. Employing a qualitative approach with a phenomenological design, the study focuses on the subjective experiences of students who actively use social media and were selected through purposive sampling. Data were collected through in-depth interviews and reflective accounts of students’ experiences, and analyzed using phenomenological procedures encompassing phenomenological reduction, meaning categorization, and the synthesis of experiential essences. The findings reveal that social media language is perceived by students as practical, comfortable, and flexible, which in turn shapes their language preferences and habitual use in daily life. These habits extend beyond digital communication and permeate oral and written interactions within the madrasah environment. The study identifies a discrepancy between students’ normative understanding of proper and correct Indonesian usage and their actual language practices, highlighting the necessity for context-sensitive pedagogical strategies in Indonesian language instruction at the Madrasah Ibtidaiyah level.